An Experimental and Analytical Study on the Compressive Behavior of Glass Fiber Reinforced Concrete (GFRC) confined with GFRP Composites - Zendaoui, Abdelhakim; Saadi, Mohamed; Yahiaoui, Djarir; Amouri, Chahinez (Engineering, Technology & Applied Science Research, 2024)
This study investigates the axial compression behavior of confined circular concrete columns through a combined experimental and analytical approach. It examines the influence of the concrete strength, 8.5, 16, and 25 MPa, internal glass fiber percentage, 0.3-1.2 %, and Glass Fiber Reinforced Polymer (GFRP) confinement thickness, 0.8, 1.6, and 2.4 mm. The Glass Fiber (GF) percentage and GFRP thickness have a significant impact on the results of the uniaxial compression tests exploring both the load-deformation behavior and crack propagation characteristics of the specimens, ranging from 90 to 110%. The proposed confinement model demonstrates excellent agreement with the experimental data for the ultimate axial strain and across the investigated range of concrete strengths.